Ecliptic North‐South Symmetry of Hydrogen Geocorona. Issue 23 (7th December 2017) - Kameda, S.; Ikezawa, S.; Sato, M.; Kuwabara, M.; Osada, N.; Murakami, G.; Yoshioka, K.; Yoshikawa, I.; Taguchi, M.; Funase, R.; Sugita, S.; Miyoshi, Y.; et al.
Abstract: The hydrogen exosphere constitutes the uppermost atmospheric layer of the Earth, and its shape may reflect the last stage of the atmospheric escape process. The distribution of hydrogen in the outer exosphere remains unobserved because outer geocoronal emissions are difficult to observe from within the exosphere. In this study, we used the Lyman Alpha Imaging Camera on board the Proximate Object Close Flyby with Optical Navigation spacecraft, located outside the exosphere, to obtain the first image of the entire geocorona that extends to more than 38 Earth radii. The observed emission intensity distribution can be reproduced using our analytical model that has three parameters: exobase temperature, exobase density, and solar radiation pressure, which implies that hot hydrogen production in the magnetized plasmasphere is not the dominant process shaping the outer hydrogen exosphere. However, the role of the magnetic effect in determining the total escape flux cannot be ruled out. Plain Language Summary: In this report, we show the first high‐quality, and wide‐field‐of‐view (FOV) image of Earth's hydrogen corona of 100 Earth radii ( RE ) obtained by the first interplanetary microspacecraft. Because hydrogen geocorona has not been observed since Apollo 16 in 1972, which observed only up to 10 R E of FOV. The field of view of our observation is 10 times wider than that in past. Furthermore, since the advancement in deep UV detection technology in the last four decades is very large, the improvement in data quality is very large. In fact, our newly obtained data strongly support a different picture for geocorona distribution. More specifically, we found that the observed ecliptic north‐south symmetrical distribution can be reproduced by a simple analytic model and is not consistent with past results. Our result strongly suggests a combination between a compact science instrument and a flexible interplanetary microspacecraft allows us to measure important scientific observables not readily accessible with conventional large‐scale spacecraft missions. Key Points: The first image of the outer hydrogen geocorona at <16 R E shows ecliptic north‐south symmetry We reproduced the observed spatial distribution using a model with neither a magnetic effect nor a satellite component Substantial contribution of the magnetic effect to the escape flux cannot be ruled out